Ranking the Indicators of the Model for Enhancing the Quality of Virtual University Education with a Knowledge Management Approach - Sadeghi Samarjani, Amir; Maghool, Ali; Karimi, Mohammad; Cherabin , Moslem (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective:  The present study aims to rank the indicators of a model for enhancing the quality of virtual university education with a knowledge management approach, conducted at the Electronic Branch of the Islamic Azad University.Methodology: This study employs a mixed-methods approach with an exploratory objective. The statistical population comprises professors and faculty members of the Electronic Branch of the Islamic Azad University, with 20 individuals purposefully selected for interviews. Data collection tools include semi-structured interviews for qualitative data and a researcher-made questionnaire for quantitative data. Qualitative data were analyzed using Glaser's (1992) coding method, while the Importance-Performance Analysis (IPA) method was applied in the quantitative phase to assess the significance and performance of the indicators. Additionally, Interpretive Structural Modeling (ISM) was utilized to stratify the dimensions of the model.Findings: The study identified 68 quality enhancement components for virtual university education. The indicator "educational system capabilities" (code 4) ranked first with a weight of 0.0294, positioned in the first quadrant of the Importance-Performance Matrix, where importance is high, but performance is low. For knowledge management indicators, "knowledge retention and prevention of misuse" (code 17) ranked first with a weight of 0.0545. Using ISM, dimensions were stratified, with "university management and leadership" placed at the highest level (Level 10) and "services and responsiveness" at the lowest level (Level 1).Conclusion: The findings highlight that knowledge management dimensions significantly impact the quality enhancement of virtual university education. The hierarchical structure underscores the importance of "university management and leadership" as a foundational element, cascading down to "services and responsiveness" as an outcome influenced by other dimensions.